CH3NH3PbI3−xClx–MoOx bulk heterojunction and its function on carrier separation actions in perovskite solar cells. (24th April 2019) - Jiang, Yurong; Feng, Yanxing; Liu, Kaikai; Qin, Chaochao; Ma, Heng
Abstract: The inverted-planar bulk heterojunction perovskite solar cells were fabricated by incorporating nanoparticle MoOx into the CH3 NH3 PbI3−x Clx perovskite active layers. The results showed that the device performances had been significantly improved, mainly reflected the enhancement of the open-circuit voltage from an average of 0.895 V to 0.959 V. This should be attributed to formation of bulk heterojunctions that can effectively separate and extract the carrier, and reduce carrier recombination. In addition, the conductive atomic force microscopy spectroscopy verified that the surface current of the perovskite-MoOx is larger than that of the pure perovskite film. The relationship between capacitance and frequency was tested and indirectly proved that bulk heterojunctions can rapidly separate the carriers. The ultrafast transient absorption spectroscopy measurements provided a reasonable explanation for the MoOx -induced rapidly separating of the carriers. Our research illustrates the application potential of bulk heterojunctions in the perovskite solar cells through doping the MoOx inorganic materials into the perovskite active layer, as well as further consolidates the role of bulk heterojunctions in perovskite active layer.